Riparian restoration benefits across space and time in subtropical Australia: From drinking water quality to wider society - Joseph M. McMahon; James C.R. Smart; Ben Stewart-Koster; Syezlin Hasan; James S. Shortle; William N. Venables; Andrew Smolders; Morag Stewart; Don Butler; Jon M. Olley; David P. Hamilton; Stuart Bunn (Ecosystem Services, 2026)

Mapping biological and chemical dimensions of antimicrobial resistance pollution and exposures due to treated wastewater discharges into US surface waters at the national scale - N.N. Khan; J. Jiang; M. Islam; H. Quon; R.L. Muenich; N. Rudko; S. Kamanmalek; J. Rice-Boayue; E. Garner; P. Westerhoff; A. Pruden; K.A. Hamilton (Environmental Pollution, 2026)

Smooth Gradients or Defined Fronts: Characterizing Within-Marsh Spatial Variability of CO2 Fluxes - Lena K. Champlin; Emily Wilson; Kenneth B. Raposa; Jason S. Goldstein; Ashley Hamilton; Jason S. Krumholz; Christopher R. Peter; Megan C. Tyrrell; Jamie M. P. Vaudrey; Robinson W. Fulweiler (Estuaries and Coasts, 2026)

Baleen Whale Occurrence in the Waters Off Virginia and North Carolina, U.S.A. From 2001 to 2019 - Sarah D. Mallette; William A. McLellan; D. Ann Pabst; M. Louise Burt; Ryan J. McAlarney; Gwendolyn G. Lockhart; Erin W. Cummings; Joel T. Bell; Matthew B. Ogburn; Philip K. Hamilton; Andrew J. Read; Robert L. Brownell; et al. (Marine Mammal Science, 2026)
Eighteen years of visual survey and strandings data were used to describe baleen whale occurrence along the continental shelf of Virginia and North Carolina, U.S.A. This region experiences heavy anthropogenic use, which poses risks for mortality and injury to baleen whales. Between 2001 and 2019, six species of baleen whales were recorded, and whales occurred year‐round. The total number of (on‐ and off‐effort) sightings and strandings amounted to 838 whales, including humpback ( Megaptera novaeangliae , n = 503) , fin ( Balaenoptera physalus , n = 197) , North Atlantic right ( Eubalaena glacialis , NARW, n = 76 ), common minke ( B. acutorostrata , n = 51), sei ( B. borealis , n = 10), and blue ( B. musculus , n = 1) whales. Spatial modeling and abundance estimates indicated whale density and distribution changed seasonally. The highest densities of all whales combined occurred in winter and spring. Across seasons, average densities were highest in the northern portion of the study area. Ninety percent of NARW sightings were outside the designated Seasonal Management Areas in place for their protection. The stranding record offered a complementary view of species richness and seasonality. This study provides a baseline of baleen whale occurrence in an area experiencing increasing anthropogenic pressures (e.g., ship traffic and offshore wind‐energy development).

Exploring trait- and state-based dietary restraint using ecological momentary assessment - Rebecca L. Elsworth; Elanor C. Hinton; Julian P. Hamilton-Shield; Natalia S. Lawrence; Jeffrey M. Brunstrom (Appetite, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

‘Earth system engineers’ and the cumulative impact of organisms in deep time - Simon A.F. Darroch; Michelle M. Casey; Alison T. Cribb; Amanda E. Bates; Matthew E. Clapham; Dori L. Contreras; Matthew Craffey; Ivo A.P. Duijnstee; William Gearty; Nicholas J. Gotelli; Marcus J. Hamilton; Riley F. Hayes; et al. (Trends in Ecology & Evolution, 2025)

GDF-15 - Implications for Bladder Cancer Care and Symptom Control - B. Foster; R. Vargas; P. Srinivasan; D. Koestler; M. Bechtel; J. Holzbeierlein; M. Fisch; N. Henry; J. Unger; J. Hamilton-Reeves (Journal of the Academy of Nutrition and Dietetics, 2025)

Menstruation and food choice: Does dietary iron selection change across menstrual cycle phases? - Jody Salton; Jeffrey M. Brunstrom; Julian P. Hamilton-Shield; Annika N. Flynn (Appetite, 2025)

Parental perspectives on the use of tumor molecular profiling and germline genetic testing during their children's cancer treatment - Marcelo M. Sleiman; Muriel R. Statman; Mary Rose Yockel; Yelena P. Wu; Jada G. Hamilton; Wendy K. Kohlmann; Jennie Vagher; Soren Feola; Luke D. Maese; Jing Chen; Burton Appel; Casey J. Mehrhoff; et al. (Familial Cancer, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Evaluating the suitability of large-scale datasets to estimate nitrogen loads and yields across different spatial scales - Andrés Felipe Suárez-Castro; Dale M. Robertson; Bernhard Lehner; Marcelo L. de Souza; Michael Kittridge; David A. Saad; Simon Linke; Rich W. McDowell; Mohammad Hassan Ranjbar; Olivier Ausseil; David P. Hamilton (Water Research, 2025)

A content analysis of parents’ reflections on pathogenic and uncertain pediatric oncology germline sequencing results - Katianne M. Howard Sharp; Mary Egan Clark; Niki Jurbergs; Annastasia Ouma; Lynn Harrison; Leslie Taylor; Kayla Hamilton; Rose B. McGee; Regina Nuccio; Stacy Hines-Dowell; Jami S. Gattuso; Michelle Pritchard; et al. (Familial Cancer, 2024)

Assessing effects of a novel weight-management product on appetite - Rebecca L. Elsworth; Elanor C. Hinton; Julian P. Hamilton-Shield; James Byrne; Camilla Easter; Hutan Ashrafian; Jeffrey M. Brunstrom (Appetite, 2024)

Palaeontological signatures of the Anthropocene are distinct from those of previous epochs - Mark Williams; Jan Zalasiewicz; Anthony D. Barnosky; Reinhold Leinfelder; Martin J. Head; Colin N. Waters; Francine M.G. McCarthy; Alejandro Cearreta; David C. Aldridge; Mary McGann; Paul B. Hamilton; Colin P. Summerhayes; et al. (Earth-Science Reviews, 2024)

Population origin and heritable effects mediate road salt toxicity and thermal stress in an amphibian - Lauren M. Conner; Debora Goedert; Sarah W. Fitzpatrick; Amber Fearnley; Emma L. Gallagher; Jessica D. Peterman; Mia E. Forgione; Sophia Kokosinska; Malik Hamilton; Lydia A. Masala; Neil Merola; Hennesy Rico; et al. (Chemosphere, 2024)

Exploring vaginal discharge scoring to assess clinical metritis severity: Comparison between intrauterine dextrose and systemic antibiotics treatments - J. Hamilton; E. Jimenez; P. Zarei; J. Lection; R. Sorto; E. Hovingh; M. Martinez; S. Bas; A.A. Barragan (The Veterinary Journal, 2024)

Development of Momentary Appetite Capture (MAC): A versatile tool for monitoring appetite over long periods - Rebecca L. Elsworth; Elanor C. Hinton; Annika N. Flynn; Lucy H. Merrell; Julian P. Hamilton-Shield; Natalia S. Lawrence; Jeffrey M. Brunstrom (Appetite, 2024)

Field-testing solutions for drinking water quality monitoring in low- and middle-income regions and case studies from Latin American, African and Asian countries - N. Pichel; F. Hymnô de Souza; L.P. Sabogal-Paz; P.K. Shah; N. Adhikari; S. Pandey; B.M. Shrestha; S. Gaihre; D.A. Pineda-Marulanda; M. Hincapie; K. Luwe; S. Kumwenda; et al. (Journal of Environmental Chemical Engineering, 2023)

Assessment of rapid wastewater surveillance for determination of communicable disease spread in municipalities - Mohsen Asadi; Daniel Hamilton; Corwyn Shomachuk; Femi F. Oloye; Chantel De Lange; Xia Pu; Charles A. Osunla; Jenna Cantin; Seba El-Baroudy; Edgard M. Mejia; Branden Gregorchuk; Michael G. Becker; et al. (Science of The Total Environment, 2023)

Overview of the search for signs of space weathering on the low-albedo asteroid (101955) Bennu - B.E. Clark; A. Sen; X.-D. Zou; D.N. DellaGiustina; S. Sugita; N. Sakatani; M. Thompson; D. Trang; E. Tatsumi; M.A. Barucci; M. Barker; H. Campins; et al. (Icarus, 2023)

A ring trial to harmonize Toxoplasma gondii microsatellite typing: comparative analysis of results and recommendations for optimization - M. Joeres; G. Cardron; K. Passebosc-Faure; N. Plault; M. Fernández-Escobar; C. M. Hamilton; L. O’Brien-Anderson; R. Calero-Bernal; L. Galal; C. Luttermann; P. Maksimov; F. J. Conraths; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)
A ring trial among five European laboratories was organized to reach consistency in microsatellite (MS) typing of the zoonotic parasite Toxoplasma gondii . Three sample sets were circulated and analyzed by each laboratory following a previously published method that is based on fragment length polymorphism of 15 MS markers. The first sample set compared typing results in general and focused on effects of DNA concentration; the second sample set focused on the polymorphic fingerprinting markers that can differentiate T. gondii strains within the same archetypal lineage; and the third set focused on non-archetypal genotypes. Methodological variations between laboratories, including the software programs used to determine MS fragment length, were collated using a questionnaire. Overall, lineage-level typing results reached a high level of agreement, especially in samples with the highest DNA concentrations. However, laboratory-specific differences were observed for particular markers. Major median differences in fragment length, of up to 6 base pairs, were related to the fluorophore used to label fragment-specific primers. In addition, primer pairs with identical sequences obtained from different suppliers resulted in fragments of differing length. Furthermore, differences in the way the sequencing profiles were assessed and interpreted may have led to deviating results in fragment length determination. Harmonization of MS typing, for example, by using the same fluorophores or by numerical adjustments applied to the fragment-lengths determined, could improve the uniformity of the results across laboratories. This is the first interlaboratory comparison, providing guidelines (added as a supplement) for the optimization of this technique.

Increasing Skin Cancer Prevention in Young Adults: the Cumulative Impact of Personalized UV Photography and MC1R Genetic Testing - Yelena P. Wu; Jada G. Hamilton; Kimberly A. Kaphingst; Jakob D. Jensen; Wendy Kohlmann; Bridget G. Parsons; Helen M. Lillie; Xuechen Wang; Benjamin Haaland; Ali P. Wankier; Douglas Grossman; Jennifer L. Hay (Journal of Cancer Education, 2023)

Social integration of translocated wildlife: a case study of rehabilitated and released elephant calves in northern Kenya - Shifra Z. Goldenberg; Stephen M. Chege; Nelson Mwangi; Ian Craig; David Daballen; Iain Douglas-Hamilton; Nadine Lamberski; Moses Lenaipa; Reuben Lendira; Colman Lesowapir; Lekilia P. Lokooria; Mathew Mutinda; et al. (Mammalian Biology, 2022)
Conservation translocations have the potential to strengthen populations of threatened and endangered species, but facilitating integration of translocated individuals with resident populations remains a substantial challenge. Developing functional social relationships like cooperative partnerships or establishing clear dominance hierarchies may be critical to integration of released individuals. Developing such relationships has not received much attention in translocation research, especially for long-lived, socially complex animals for which establishment and navigation of social environments is often a lengthy process that requires sustained monitoring to understand. Here, we present a case study of the social associations of African savannah elephant ( Loxodonta africana ) calves that have been rehabilitated and released into a fenced wildlife sanctuary in northern Kenya with a resident population of elephants. We use focal follows of interactions pre-release and GPS tracking post-release to quantify social associations of calves with each other and with resident elephants at the release site. We demonstrate how this approach supports translocation monitoring by capturing temporal trends in social patterns within and between release cohorts and among released elephants and wild elephants already resident at the site during a transitional soft release period. Our results show that initial post-release social behavior of rehabilitated calves is related to histories of interaction with familiar individuals and cohort membership and that released calves increased their associations with residents over time. This information provides new behavioral insights for guiding elephant release projects, like the strength of relationships within and among release cohorts, the time to integration with the resident population, and the occurrence and increased incidence of societal fission–fusion. Further, this study provides an example of the utility of animal behavior research to achieve and assess progress towards conservation objectives, and to develop monitoring tools for conservation managers.

Climate impacts alter fisheries productivity and turnover on coral reefs - Mark Hamilton; James P. W. Robinson; Cassandra E. Benkwitt; Shaun K. Wilson; M. Aaron MacNeil; Ameer Ebrahim; Nicholas A. J. Graham (Coral Reefs, 2022)
Alteration of benthic reef habitat after coral bleaching and mortality induces changes in fish assemblages, with implications for fisheries. Our understanding of climate impacts to coral reef fisheries is largely based on fish abundance and biomass. The rates at which biomass is produced and replenished (productivity and turnover) are also important to sustaining fisheries, yet the responses of these metrics following bleaching are largely unknown. Here, we examine changes in fish productivity and turnover after mass coral bleaching events in Seychelles, on reefs that were recovering to coral-dominated habitats and those that shifted to macroalgae-dominated regimes. Productivity of fish assemblages increased on all recovering reefs, particularly on fished reefs resulting in levels similar to protected reefs 19 years after bleaching. Herbivore-detritivores, such as scraping and excavating parrotfish, appeared to drive biomass production through increased abundance on recovering reefs. Productivity on regime-shifted reefs remained stable at 1994 levels in fished areas, with increases observed on protected reefs. Large increases in browser productivity (particularly on protected reefs), combined with increases for invertivores, maintained post-bleaching productivity on macroalgal reefs. For all diet groups, net turnover was generally higher on fished regime-shifted reefs than on recovering reefs, suggesting fish biomass is more readily replenished on macroalgal reefs. Reef structural complexity was a positive predictor of productivity for all diet groups. These findings indicate that post-bleaching reef fish productivity is strongly influenced by benthic recovery trajectories, and demonstrates the importance of herbivore and invertivore species in sustaining small-scale inshore fisheries following climatic disturbances.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Estimated life-history traits and movements of the Caribbean reef shark (Carcharhinus perezi) in The Bahamas based on tag-recapture data - Brendan S. Talwar; Darcy Bradley; Christopher Berry; Mark E. Bond; Ian A. Bouyoucos; Annabelle M. L. Brooks; Candace Y. A. Fields; Austin J. Gallagher; Tristan L. Guttridge; Annie E. Guttridge; Neil Hammerschlag; Ian Hamilton; et al. (Marine Biology, 2022)

Restoring shallow lakes impaired by eutrophication: Approaches, outcomes, and challenges - Jonathan M. Abell; Deniz Özkundakci; David P. Hamilton; Paula Reeves (Critical Reviews in Environmental Science and Technology, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Global co‐occurrence of methanogenic archaea and methanotrophic bacteria in Microcystis aggregates - Chuang Li; K. David Hambright; Hannah G. Bowen; Majoi A. Trammell; Hans‐Peter Grossart; Michele A. Burford; David P. Hamilton; Helong Jiang; Delphine Latour; Elisabeth I. Meyer; Judit Padisák; Richard M. Zamor; et al. (Environmental Microbiology, 2021)
Summary Global warming and eutrophication contribute to the worldwide increase in cyanobacterial blooms, and the level of cyanobacterial biomass is strongly associated with rises in methane emissions from surface lake waters. Hence, methane‐metabolizing microorganisms may be important for modulating carbon flow in cyanobacterial blooms. Here, we surveyed methanogenic and methanotrophic communities associated with floating Microcystis aggregates in 10 lakes spanning four continents, through sequencing of 16S rRNA and functional marker genes. Methanogenic archaea (mainly Methanoregula and Methanosaeta ) were detectable in 5 of the 10 lakes and constituted the majority (~50%–90%) of the archaeal community in these lakes. Three of the 10 lakes contained relatively more abundant methanotrophs than the other seven lakes, with the methanotrophic genera Methyloparacoccus , Crenothrix , and an uncultured species related to Methylobacter dominating and nearly exclusively found in each of those three lakes. These three are among the five lakes in which methanogens were observed. Operational taxonomic unit (OTU) richness and abundance of methanotrophs were strongly positively correlated with those of methanogens, suggesting that their activities may be coupled. These Microcystis ‐aggregate‐associated methanotrophs may be responsible for a hitherto overlooked sink for methane in surface freshwaters, and their co‐occurrence with methanogens sheds light on the methane cycle in cyanobacterial aggregates.

Coastal Ocean Observing and Modeling Systems in Brazil: Initiatives and Future Perspectives - Guilherme Franz; Carlos A. E. Garcia; Janini Pereira; Luiz Paulo de Freitas Assad; Marcelo Rollnic; Luis Hamilton P. Garbossa; Letícia Cotrim da Cunha; Carlos A. D. Lentini; Paulo Nobre; Alexander Turra; Janice R. Trotte-Duhá; Mauro Cirano; et al. (Frontiers in Marine Science, 2021)
Coastal ocean observing and modeling systems (coastal observatories), connected with regional and global ocean systems, improve the quality of information and forecasts for effective management of safe and sustainable maritime activities. The public availability of systematic and long-term information of the ocean is an engine for the Blue Economy, boosting economic growth, employment, and innovation. An overview of some Brazilian initiatives is presented in this paper, involving universities, private companies, federal and state agencies, covering institutions from south to north of Brazil. Although these initiatives focus mainly on ocean physics, integrated efforts can extend the scope to include biogeochemistry and marine biodiversity, helping to address interdisciplinary problems. Existing initiatives can be connected, and new ones fostered, to fill in the gaps of temporal and spatial coverage of ocean monitoring in the vast oceanic area under Brazilian jurisdiction (nationally referred to as the Blue Amazon, in reference to the similar richness of the Amazon Forest). The alignment among national and regional initiatives, as well as with international programs, can be promoted if coordinated by a national-level organization, maximizing the return of public investment and socioeconomic benefits. In light of international examples, possible future institutional arrangements are discussed, leveraging from existing national public policies and international cooperation that Brazil is taking part. The United Nations Decade of Ocean Science for Sustainable Development is a timely opportunity to encourage an institutional arrangement to support and articulate an integrated network of coastal observatories in Brazil.

The Society for Environmental Geochemistry and Health (SEGH): building for the future of early career researchers - O. S. Humphrey; D. R. S. Middleton; S. Ahmad; T. Cocerva; S. M. Dowell; R. Garza-Galndo; E. M. Hamilton; N. Kafwamfwa; B. Kaninga; P. Kourgia; I. S. Ligowe; H. A. MacLeod; et al. (Environmental Geochemistry and Health, 2021)

Spatial analysis of urine zinc (Zn) concentration for women of reproductive age and school age children in Malawi - Felix P. Phiri; E. Louise Ander; R. Murray Lark; Edward J. M. Joy; Alexander A. Kalimbira; Parminder S. Suchdev; Jellita Gondwe; Elliott M. Hamilton; Michael J. Watts; Martin R. Broadley (Environmental Geochemistry and Health, 2021)
Zinc (Zn) is an essential micronutrient, and Zn deficiency remains a major global public health challenge. Recognised biomarkers of population Zn status include blood plasma or serum Zn concentration and proxy data such as dietary Zn intake and prevalence of stunting. Urine Zn concentration is rarely used to assess population Zn status. This study assessed the value of urine Zn concentration as a biomarker of population Zn status using a nationally representative sample of non-pregnant women of reproductive age (WRA) and school-aged children (SAC) in Malawi. Spot (casual) urine samples were collected from 741 WRA and 665 SAC. Urine Zn concentration was measured by inductively coupled plasma mass spectrometry with specific gravity adjustment for hydration status. Data were analysed using a linear mixed model with a spatially correlated random effect for between-cluster variation. The effect of time of sample collection (morning or afternoon), and gender (for SAC), on urine Zn concentration were examined. There was spatial dependence in urine Zn concentration between clusters among SAC but not WRA, which indicates that food system or environmental factors can influence urine Zn concentration. Mapping urine Zn concentration could potentially identify areas where the prevalence of Zn deficiency is greater and thus where further sampling or interventions might be targeted. There was no evidence for differences in urine Zn concentration between gender ( P = 0.69) or time of sample collection ( P = 0.85) in SAC. Urine Zn concentration was greater in afternoon samples for WRA ( P = 0.003). Relationships between urine Zn concentration, serum Zn concentration, dietary Zn intake, and potential food systems covariates warrant further study.

Reference and current Trophic Level Index of New Zealand lakes: benchmarks to inform lake management and assessment - Jonathan M. Abell; Paul van Dam‐Bates; Deniz Özkundakci; David P. Hamilton (New Zealand Journal of Marine and Freshwater Research, 2020)
Knowledge of trophic status is fundamental to understanding the condition and function of lake ecosystems. We developed regression models to predict chlorophyll a concentrations (chl a ) in New Zealand lakes for reference and current states, based on an existing dataset of total nitrogen (TN) and total phosphorus (TP) concentrations for 1031 lakes. Models were then developed to predict Secchi depth based on chl a and a sediment resuspension term applicable to shallow lakes. Estimates of all four Trophic Level Index (TLI) variables (chl a , TN, TP and Secchi depth) were analysed to estimate reference and current state TLI for the nationally representative sample of 1031 lakes. There was a trend of eutrophication between reference and current states, with systematic differences among lake geomorphic types. Mean chl a increased 3.5‐fold (2.42 mg m −3 vs. 8.32 mg m −3 ) and mean Secchi depth decreased (indicating lower clarity) by approximately one‐third (9.62 m vs. 6.48 m) between reference and current states. On average, TLI increased by 0.67, with the TLI increase >1 in approximately one‐third (31%) of lakes. This study informs the status of lake ecosystems in NZ and provides benchmarks to guide management and assessment.

Effects of hypoxia on the behavior and physiology of kelp forest fishes - Evan G. Mattiasen; Neosha S Kashef; David M. Stafford; Cheryl A. Logan; Susan M. Sogard; Eric P. Bjorkstedt; Scott L. Hamilton (Global Change Biology, 2020)
Forecasts from climate models and oceanographic observations indicate increasing deoxygenation in the global oceans and an elevated frequency and intensity of hypoxic events in the coastal zone, which have the potential to affect marine biodiversity and fisheries. Exposure to low dissolved oxygen (DO) conditions may have deleterious effects on early life stages in fishes. This study aims to identify thresholds to hypoxia while testing behavioral and physiological responses of two congeneric species of kelp forest fish to four DO levels, ranging from normoxic to hypoxic (8.7, 6.0, 4.1, and 2.2 mg O 2 /L). Behavioral tests identified changes in exploratory behavior and turning bias (lateralization), whereas physiological tests focused on determining changes in hypoxia tolerance (pCrit), ventilation rates, and metabolic rates, with impacts on the resulting capacity for aerobic activity. Our findings indicated that copper rockfish ( Sebastes caurinus ) and blue rockfish ( Sebastes mystinus ) express sensitivity to hypoxia; however, the strength of the response differed between species. Copper rockfish exhibited reduced absolute lateralization and increased escape time at the lowest DO levels, whereas behavioral metrics for blue rockfish did not vary with oxygen level. Both species exhibited decreases in aerobic scope (as a function of reduced maximum metabolic rate) and increases in ventilation rates to compensate for decreasing oxygen levels. Blue rockfish had a lower pCrit and stronger acclimation response compared to copper rockfish. The differences expressed by each species suggest that acclimatization to changing ocean conditions may vary, even among related species that recruit to the same kelp forest habitat, leading to winners and losers under future ocean conditions. Exposure to hypoxia can decrease individual physiological fitness through metabolic and aerobic depression and changes to anti‐predator behavior, with implications for the outcome of ecological interactions and the management of fish stocks in the face of climate change.

Are anglers exposed to Escherichia coli from an agriculturally impacted river? - Bonnie M. Hamilton; Amanda D. Harwood; Hunter R. Wilson; Timothy P. Keeton; Murray C. Borrello (Environmental Monitoring and Assessment, 2020)

Feral cat eradication on Dirk Hartog Island, Western Australia - D. Algar; M. Johnston; C. Tiller; M. Onus; J. Fletcher; G. Desmond; N. Hamilton; P. Speldewinde (Biological Invasions, 2020)

Differences in postural sway among healthy adults are associated with the ability to perform steady contractions with leg muscles - Leah A. Davis; Stephen P. Allen; Landon D. Hamilton; Alena M. Grabowski; Roger M. Enoka (Experimental Brain Research, 2020)

Quantitative trait loci and differential gene expression analyses reveal the genetic basis for negatively associated β-carotene and starch content in hexaploid sweetpotato [Ipomoea batatas (L.) Lam.] - Dorcus C. Gemenet; Guilherme da Silva Pereira; Bert De Boeck; Joshua C. Wood; Marcelo Mollinari; Bode A. Olukolu; Federico Diaz; Veronica Mosquera; Reuben T. Ssali; Maria David; Mercy N. Kitavi; Gabriela Burgos; et al. (Theoretical and Applied Genetics, 2020)
Key message β-Carotene content in sweetpotato is associated with the Orange and phytoene synthase genes; due to physical linkage of phytoene synthase with sucrose synthase , β-carotene and starch content are negatively correlated. Abstract In populations depending on sweetpotato for food security, starch is an important source of calories, while β-carotene is an important source of provitamin A. The negative association between the two traits contributes to the low nutritional quality of sweetpotato consumed, especially in sub-Saharan Africa. Using a biparental mapping population of 315 F 1 progeny generated from a cross between an orange-fleshed and a non-orange-fleshed sweetpotato variety, we identified two major quantitative trait loci (QTL) on linkage group (LG) three (LG3) and twelve (LG12) affecting starch, β-carotene, and their correlated traits, dry matter and flesh color. Analysis of parental haplotypes indicated that these two regions acted pleiotropically to reduce starch content and increase β-carotene in genotypes carrying the orange-fleshed parental haplotype at the LG3 locus. Phytoene synthase and sucrose synthase, the rate-limiting and linked genes located within the QTL on LG3 involved in the carotenoid and starch biosynthesis, respectively, were differentially expressed in Beauregard versus Tanzania storage roots. The Orange gene, the molecular switch for chromoplast biogenesis, located within the QTL on LG12 while not differentially expressed was expressed in developing roots of the parental genotypes. We conclude that these two QTL regions act together in a cis and trans manner to inhibit starch biosynthesis in amyloplasts and enhance chromoplast biogenesis, carotenoid biosynthesis, and accumulation in orange-fleshed sweetpotato. Understanding the genetic basis of this negative association between starch and β-carotene will inform future sweetpotato breeding strategies targeting sweetpotato for food and nutritional security.

The global Microcystis interactome - Katherine V. Cook; Chuang Li; Haiyuan Cai; Lee R. Krumholz; K. David Hambright; Hans W. Paerl; Morgan M. Steffen; Alan E. Wilson; Michele A. Burford; Hans‐Peter Grossart; David P. Hamilton; Helong Jiang; et al. (Limnology and Oceanography, 2020)
Bacteria play key roles in the function and diversity of aquatic systems, but aside from study of specific bloom systems, little is known about the diversity or biogeography of bacteria associated with harmful cyanobacterial blooms (cyanoHABs). CyanoHAB species are known to shape bacterial community composition and to rely on functions provided by the associated bacteria, leading to the hypothesized cyanoHAB interactome, a coevolved community of synergistic and interacting bacteria species, each necessary for the success of the others. Here, we surveyed the microbiome associated with Microcystis aeruginosa during blooms in 12 lakes spanning four continents as an initial test of the hypothesized Microcystis interactome. We predicted that microbiome composition and functional potential would be similar across blooms globally. Our results, as revealed by 16S rRNA sequence similarity, indicate that M. aeruginosa is cosmopolitan in lakes across a 280° longitudinal and 90° latitudinal gradient. The microbiome communities were represented by a wide range of operational taxonomic units and relative abundances. Highly abundant taxa were more related and shared across most sites and did not vary with geographic distance, thus, like Microcystis , revealing no evidence for dispersal limitation. High phylogenetic relatedness, both within and across lakes, indicates that microbiome bacteria with similar functional potential were associated with all blooms. While Microcystis and the microbiome bacteria shared many genes, whole‐community metagenomic analysis revealed a suite of biochemical pathways that could be considered complementary. Our results demonstrate a high degree of similarity across global Microcystis blooms, thereby providing initial support for the hypothesized Microcystis interactome.

Prevalence and Genetic Diversity of Toxoplasma gondii in Free-Ranging Chickens from the Caribbean - C. M. Hamilton; R. Robins; R. Thomas; C. Oura; S. Oliveira; I. Villena; E. A. Innes; F. Katzer; P. J. Kelly (Acta Parasitologica, 2019)

Algal scavenging of mercury in preindustrial Arctic lakes - P. M. Outridge; G. A. Stern; P. B. Hamilton; H. Sanei (Limnology and Oceanography, 2019)
The geochemical speciation of total mercury (THg) was examined in pre‐1800 Arctic lake sediments to improve understanding of the factors controlling “natural baseline” THg. Solid‐phase binding forms of THg were determined by sequential extraction of dated cores from three lakes in different ecozones (barren tundra, grassy tundra, and boreal forest). Sediment organic matter (OM) was mostly of algal origin. Mercury was highly concentrated in the sediment OM fraction (OM‐Hg), comprising 60–87% of THg, while OM (as total organic carbon) constituted only 0.6–13% of sediment dry weight (DW). OM‐Hg concentrations were equivalent to 159 ± 13 to 776 ± 215 ng Hg g −1 DW in algal OM and were enriched 2–39 times compared to sediment THg, indicating that even small changes in algal OM inputs could significantly alter THg. OM‐Hg explained 76–96% of the variation in THg concentrations over many centuries. Concentrations of S2 carbon (an algal productivity proxy) and OM‐Hg were significantly correlated in two lakes but not in the boreal forest lake possibly because of OM remineralization in its deep water column. Fluxes of S2 carbon, OM‐Hg, and THg were highly correlated in the barren tundra lake but could not be calculated for the other lakes. The results overall indicate that high algal Hg concentrations due to scavenging of available Hg controlled OM‐Hg flux to sediments, thus driving changes in THg concentrations and fluxes. These findings improve our understanding of the long‐term stability of baseline THg in northern lakes under a changing climate, including in the modern era.

Comparison of Unyvero P55 Pneumonia Cartridge, in-house PCR and culture for the identification of respiratory pathogens and antibiotic resistance in bronchoalveolar lavage fluids in the critical care setting - Naomi J. Gadsby; Martin P. McHugh; Callum Forbes; Laura MacKenzie; Stephen K. D. Hamilton; David M. Griffith; Kate E. Templeton (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Constructed treatment wetlands provide habitat for zooplankton communities in agricultural peat lake catchments - Rebecca S. Eivers; Ian C. Duggan; David P. Hamilton; John M. Quinn (Wetlands, 2018)

Sensor manufacturer, temperature, and cyanobacteria morphology affect phycocyanin fluorescence measurements - Caroline M. Hodges; Susanna A. Wood; Jonathan Puddick; Christopher G. McBride; David P. Hamilton (Environmental Science and Pollution Research, 2018)

Indigenous arthropod natural enemies of the invasive brown marmorated stink bug in North America and Europe - Paul K. Abram; Kim A. Hoelmer; Angelita Acebes-Doria; Heather Andrews; Elizabeth H. Beers; J. Christopher Bergh; Ric Bessin; David Biddinger; Paul Botch; Matthew L. Buffington; Mary L. Cornelius; Elena Costi; et al. (Journal of Pest Science, 2017)

Establishment and characterization of a platinum- and paclitaxel-resistant high grade serous ovarian carcinoma cell line - Pang-Ning Teng; Nicholas W. Bateman; Guisong Wang; Tracy Litzi; Brian E. Blanton; Brian L. Hood; Kelly A. Conrads; Wei Ao; Kate E. Oliver; Kathleen M. Darcy; William P. McGuire; Keren Paz; et al. (Human Cell, 2017)

Multiple lines of evidence determine robust nutrient load limits required to safeguard a threatened lake/lagoon system - M. Schallenberg; D. P. Hamilton; A. S. Hicks; H. A. Robertson; M. Scarsbrook; B. Robertson; K. Wilson; D. Whaanga; H. F. E. Jones; K. Hamill (New Zealand Journal of Marine and Freshwater Research, 2017)
Three independent scientific lines of evidence were sought to determine the nutrient load limits to safeguard the macrophyte community of an intermittently closed and open lake/lagoon (ICOLL): (1) a literature review identified nitrogen load thresholds related to the collapse of macrophytes in similar systems in Australia, Europe and elsewhere, (2) an ICOLL expert carried out an assessment based on current local data and on data from 57 Australian coastal lakes and lagoons, and (3) a deterministic coupled hydrodynamic‐ecological model was developed and applied to simulate the ecological outcomes of several nutrient loading scenarios. The three lines of evidence converged on well‐defined nitrogen load estimates required to avoid the collapse of the macrophyte community. Uncertainties were slightly greater in relation to required phosphorus load limits, but the evidence still helped set a precautionary phosphorus load limit that accounted for these uncertainties. Thus, despite the challenges in setting load limits for complex ecosystems, multiple lines of evidence helped derive robust nutrient load limits for managing the ICOLL to safeguard values associated with a healthy macrophyte community.

Variability in the chemistry of private drinking water supplies and the impact of domestic treatment systems on water quality - E. L. Ander; M. J. Watts; P. L. Smedley; E. M. Hamilton; R. Close; H. Crabbe; T. Fletcher; A. Rimell; M. Studden; G. Leonardi (Environmental Geochemistry and Health, 2016)

Guiding principles for the development and application of solid-phase phosphorus adsorbents for freshwater ecosystems - G. B. Douglas; D. P. Hamilton; M. S. Robb; G. Pan; B. M. Spears; M. Lurling (Aquatic Ecology, 2016)

A rapid PCR-based test for identification of fifteen British bat species - P. B. Hamilton; T. M. Uren Webster; M. Basiewicz; E. V. Kennedy; E. S. R. De-Bastos; F. Mathews (Conservation Genetics Resources, 2015)

Does flood rhythm drive ecosystem responses in tropical riverscapes? - Timothy D. Jardine; Nicholas R. Bond; Michele A. Burford; Mark J. Kennard; Douglas P. Ward; Peter Bayliss; Peter M. Davies; Michael M. Douglas; Stephen K. Hamilton; John M. Melack; Robert J. Naiman; Neil E. Pettit; et al. (Ecology, 2015)
Biotic communities are shaped by adaptations from generations of exposure to selective pressures by recurrent and often infrequent events. In large rivers, floods can act as significant agents of change, causing considerable physical and biotic disturbance while often enhancing productivity and diversity. We show that the relative balance between these seemingly divergent outcomes can be explained by the rhythmicity, or predictability of the timing and magnitude, of flood events. By analyzing biological data for large rivers that span a gradient of rhythmicity in the Neotropics and tropical Australia, we find that systems with rhythmic annual floods have higher fish species richness, more stable avian populations, and elevated rates of riparian forest production compared with those with arrhythmic flood pulses. Intensification of the hydrological cycle driven by climate change, coupled with reductions in runoff due to water extractions for human use and altered discharge from impoundments, is expected to alter the hydrologic rhythmicity of floodplain rivers with significant consequences for both biodiversity and productivity.

Organic matter stocks increase with degree of invasion in temperate inland wetlands - J. P. Martina; S. K. Hamilton; M. R. Turetsky; C. J. Phillippo (Plant and Soil, 2014)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

The diet of M yotis lucifugus across C anada: assessing foraging quality and diet variability - Elizabeth L. Clare; William O. C. Symondson; Hugh Broders; François Fabianek; Erin E. Fraser; Alistair MacKenzie; Andrew Boughen; Rachel Hamilton; Craig K. R. Willis; Felix Martinez‐Nuñez; Allyson K. Menzies; Kaleigh J. O. Norquay; et al. (Molecular Ecology, 2014)
Variation in prey resources influences the diet and behaviour of predators. When prey become limiting, predators may travel farther to find preferred food or adjust to existing local resources. When predators are habitat limited, local resource abundance impacts foraging success. We analysed the diet of Myotis lucifugus (little brown bats) from Nova Scotia (eastern Canada) to the Northwest Territories (north‐western Canada). This distribution includes extremes of season length and temperature and encompasses colonies on rural monoculture farms, and in urban and unmodified areas. We recognized nearly 600 distinct species of prey, of which ≈30% could be identified using reference sequence libraries. We found a higher than expected use of lepidopterans, which comprised a range of dietary richness from ≈35% early in the summer to ≈55% by late summer. Diptera were the second largest prey group consumed, representing ≈45% of dietary diversity early in the summer. We observed extreme local dietary variability and variation among seasons and years. Based on the species of insects that were consumed, we observed that two locations support prey species with extremely low pollution and acidification tolerances, suggesting that these are areas without environmental contamination. We conclude that there is significant local population variability in little brown bat diet that is likely driven by seasonal and geographical changes in insect diversity, and that this prey may be a good indicator of environment quality.

A framework for testing the ability of models to project climate change and its impacts - J. C. Refsgaard; H. Madsen; V. Andréassian; K. Arnbjerg-Nielsen; T. A. Davidson; M. Drews; D. P. Hamilton; E. Jeppesen; E. Kjellström; J. E. Olesen; T. O. Sonnenborg; D. Trolle; et al. (Climatic Change, 2014)

Conserving large populations of lions – the argument for fences has holes - S. Creel; M. S. Becker; S. M. Durant; J. M'Soka; W. Matandiko; A. J. Dickman; D. Christianson; E. Dröge; T. Mweetwa; N. Pettorelli; E. Rosenblatt; P. Schuette; et al. (Ecology Letters, 2013)
Packer et al . reported that fenced lion populations attain densities closer to carrying capacity than unfenced populations. However, fenced populations are often maintained above carrying capacity, and most are small. Many more lions are conserved per dollar invested in unfenced ecosystems, which avoid the ecological and economic costs of fencing.

Ecosystem respiration: Drivers of daily variability and background respiration in lakes around the globe - Christopher T. Solomon; Denise A. Bruesewitz; David C. Richardson; Kevin C. Rose; Matthew C. Van de Bogert; Paul C. Hanson; Timothy K. Kratz; Bret Larget; Rita Adrian; Brenda Leroux Babin; Chih-Yu Chiu; David P. Hamilton; et al. (Limnology and Oceanography, 2013)
We assembled data from a global network of automated lake observatories to test hypotheses regarding the drivers of ecosystem metabolism. We estimated daily rates of respiration and gross primary production (GPP) for up to a full year in each lake, via maximum likelihood fits of a free‐water metabolism model to continuous high‐frequency measurements of dissolved oxygen concentrations. Uncertainties were determined by a bootstrap analysis, allowing lake‐days with poorly constrained rate estimates to be down‐weighted in subsequent analyses. GPP and respiration varied considerably among lakes and at seasonal and daily timescales. Mean annual GPP and respiration ranged from 0.1 to 5.0 mg O 2 L −1 d −1 and were positively related to total phosphorus but not dissolved organic carbon concentration. Within lakes, significant day‐to‐day differences in respiration were common despite large uncertainties in estimated rates on some lake‐days. Daily variation in GPP explained 5% to 85% of the daily variation in respiration after temperature correction. Respiration was tightly coupled to GPP at a daily scale in oligotrophic and dystrophic lakes, and more weakly coupled in mesotrophic and eutrophic lakes. Background respiration ranged from 0.017 to 2.1 mg O 2 L −1 d −1 and was positively related to indicators of recalcitrant allochthonous and autochthonous organic matter loads, but was not clearly related to an indicator of the quality of allochthonous organic matter inputs.

Case studies of scenario analysis for adaptive management of natural resource and infrastructure systems - Michelle C. Hamilton; Shital A. Thekdi; Elisabeth M. Jenicek; Russell S. Harmon; Michael E. Goodsite; Michael P. Case; Christopher W. Karvetski; James H. Lambert (Environment Systems and Decisions, 2013)

The role of relatedness in structuring the social network of a wild guppy population - Darren P. Croft; P. B. Hamilton; S. K. Darden; D. M. P. Jacoby; R. James; E. M. Bettaney; C. R. Tyler (Oecologia, 2012)

Enhancing a Cancer Prevention and Control Curriculum Through Interactive Group Discussions - L. P. Forsythe; S. M. Gadalla; J. G. Hamilton; B. M. Heckman-Stoddard; E. E. Kent; G. Y. Lai; S. W. Lin; P. Luhn; J. M. Faupel-Badger (Journal of Cancer Education, 2012)

Mapping the biosphere: exploring species to understand the origin, organization and sustainability of biodiversity - Q. D. Wheeler; S. Knapp; D. W. Stevenson; J. Stevenson; S. D. Blum; B. M. Boom; G. G. Borisy; J. L. Buizer; M. R. De Carvalho; A. Cibrian; M. J. Donoghue; V. Doyle; et al. (Systematics and Biodiversity, 2012)

A community-based framework for aquatic ecosystem models - Dennis Trolle; David P. Hamilton; Matthew R. Hipsey; Karsten Bolding; Jorn Bruggeman; Wolf M. Mooij; Jan H. Janse; Anders Nielsen; Erik Jeppesen; J. Alex Elliott; Vardit Makler-Pick; Thomas Petzoldt; et al. (Hydrobiologia, 2012)

Landsat remote sensing of chlorophyll a concentrations in central North Island lakes of New Zealand - M. G. Allan; D. P. Hamilton; B. J. Hicks; L. Brabyn (International Journal of Remote Sensing, 2011)

Preface: Lake restoration: an experimental ecosystem approach for eutrophication control - D. P. Hamilton; M. J. Landman (Hydrobiologia, 2011)

Hypolimnetic phosphorus and nitrogen dynamics in a small, eutrophic lake with a seasonally anoxic hypolimnion - Deniz Özkundakci; David P. Hamilton; Max M. Gibbs (Hydrobiologia, 2011)

Nitrogen and Phosphorus Limitation of Phytoplankton Growth in New Zealand Lakes: Implications for Eutrophication Control - Jonathan M. Abell; Deniz Özkundakci; David P. Hamilton (Ecosystems, 2010)

Research partnerships with local communities: two case studies from Papua New Guinea and Australia - G. R. Almany; R. J. Hamilton; D. H. Williamson; R. D. Evans; G. P. Jones; M. Matawai; T. Potuku; K. L. Rhodes; G. R. Russ; B. Sawynok (Coral Reefs, 2010)

Challenges and opportunities for integrating lake ecosystem modelling approaches - Wolf M. Mooij; Dennis Trolle; Erik Jeppesen; George Arhonditsis; Pavel V. Belolipetsky; Deonatus B. R. Chitamwebwa; Andrey G. Degermendzhy; Donald L. DeAngelis; Lisette N. De Senerpont Domis; Andrea S. Downing; J. Alex Elliott; Carlos Ruberto Fragoso; et al. (Aquatic Ecology, 2010)

Nutrient limitation of phytoplankton in solar salt ponds in Shark Bay, Western Australia - Richard D. Segal; Anya M. Waite; David P. Hamilton (Hydrobiologia, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Genetic variation in strains of zebrafish (Danio rerio) and the implications for ecotoxicology studies - T. S. Coe; P. B. Hamilton; A. M. Griffiths; D. J. Hodgson; M. A. Wahab; C. R. Tyler (Ecotoxicology, 2009)

Low‐dose alum application trialled as a management tool for internal nutrient loads in Lake Okaro, New Zealand - W. J. Paul; D. P. Hamilton; M. M. Gibbs (New Zealand Journal of Marine and Freshwater Research, 2008)
Aluminium sulfate (alum) was applied to Lake Okaro, a eutrophic New Zealand lake with recurrent cyanobacterial blooms, to evaluate its suitability for reducing trophic status and bloom frequency. The dose yielded 0.6 g aluminium m ‐3 in the epilimnion Before dosing, pH exceeded 8 in epilimnetic waters but was optimal for flocculation (6–8) below 4 m depth. After dosing, there was no significant change in water clarity, hypolimnetic pH decreased to 5.5 , and soluble aluminium exceeded recommended guidelines for protection of freshwater organisms. Epilimnetic phosphate concentrations decreased from 40 to 5 mg m ‐3 and total nitrogen (TN):total phosphorus (TP) mass ratios increased from 7:1 to 37:1. The dominant phytoplankton species changed from Anabaena spp. before dosing, to Ceratium hirudinella , then Staurastrum sp. after dosing. Detection of effectiveness of dosing may have been limited by sampling duration and design, as well as the low alum dose. The decrease in hypolimnetic pH and epilimnetic TP, and increase in Al 3+ and chlorophyll a , are attributed to the low alkalinity lake water and coincidence of alum dosing with a cyanobacterial bloom and high pH.

The effects of CYP3A4 inhibition on erlotinib pharmacokinetics: computer-based simulation (SimCYP™) predicts in vivo metabolic inhibition - Ashok Rakhit; Michael P. Pantze; Scott Fettner; Hannah M. Jones; Jean-Eric Charoin; Myriam Riek; Bert L. Lum; Marta Hamilton (European Journal of Clinical Pharmacology, 2008)

Cooling lakes while the world warms: Effects of forest regrowth and increased dissolved organic matter on the thermal regime of a temperate, urban lake - Tanentzap Andrew J.; Yan Norman D.; Bill Keller; Robert Girard; Jocelyne Heneberry; John M. Gunn; David P. Hamilton; Peter A. Taylor (Limnology and Oceanography, 2008)
Depending on the magnitudes and directions of changes in air temperatures, winds, and underwater light attenuation, lakes may either warm or cool. Here we report a 28‐yr decrease in the whole‐lake average temperature of Clearwater Lake, Canada, despite regional signatures of climate warming. Using a one‐dimensional lake mixing model, we demonstrate that this pattern was attributable to a 35% reduction in surface wind speeds, itself explained by forest regrowth following local SO 2 emission reductions and tree planting, and a 10‐fold increase in dissolved organic carbon concentrations causing a substantial increase in vertical light attenuation following deacidification of the lake. Long‐term trends in lake temperatures do not necessarily follow those of air temperatures. The Clearwater Lake data demonstrate that any factors that influence local wind speeds and underwater light attenuation should be considered as modifiers of the effects of climate warming on lake thermal regimes.

Patterns of male reproductive success in a highly promiscuous whale species: the endangered North Atlantic right whale - T. R. FRASIER; P. K. HAMILTON; M. W. BROWN; L. A. CONGER; A. R. KNOWLTON; M. K. MARX; C. K. SLAY; S. D. KRAUS; B. N. WHITE (Molecular Ecology, 2007)
Parentage analyses of baleen whales are rare, and although mating systems have been hypothesized for some species, little data on realized male reproductive success are available and the patterns of male reproductive success have remained elusive for most species. Here we combine over 20 years of photo‐identification data with high‐resolution genetic data for the majority of individual North Atlantic right whales to assess paternity in this endangered species. There was significant skew in male reproductive success compared to what would be expected if mating was random ( P 0.001). The difference was due to an excess of males assigned zero paternities, a deficiency of males assigned one paternity, and an excess of males assigned as fathers for multiple calves. The variance in male reproductive success was high relative to other aquatically mating marine mammals, but was low relative to mammals where the mating system is based on resource‐ and/or mate‐defence polygyny. These results are consistent with previous data suggesting that the right whale mating system represents one of the most intense examples of sperm competition in mammals, but that sperm competition on its own does not allow for the same degree of polygyny as systems where males can control access to resources and/or mates. The age distribution of assigned fathers was significantly biased towards older males ( P 0.05), with males not obtaining their first paternity until ~15 years of age, which is almost twice the average age of first fertilization in females (8 years), suggesting that mate competition is preventing younger males from reproducing. The uneven distribution of paternities results in a lower effective population size in this species that already has one of the lowest reported levels of genetic diversity, which may further inhibit reproductive success through mate incompatibility of genetically similar individuals.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Benthic nutrient fluxes in a eutrophic, polymictic lake - D. F. Burger; D. P. Hamilton; C. A. Pilditch; M. M. Gibbs (Hydrobiologia, 2007)

Empirical indices of spatial and executive processes in visuo-spatial working memory - J. M. Thompson; C. J. Hamilton; J. M. Gray; J. G. Quinn; P. Mackin; I. N. Ferrier; A. H. Young (Cognitive Processing, 2006)

Annual basal area increment and growth duration of Pinus taeda in response to eight years of free‐air carbon dioxide enrichment - DAVID J. P. MOORE; SUSANNE AREF; RINGO M. HO; JEFFREY S. PIPPEN; JASON G. HAMILTON; EVAN H. DE LUCIA (Global Change Biology, 2006)
Rising CO 2 is predicted to increase forest productivity, although the duration of the response and how it might be altered by variation in rainfall, temperature and other environmental variables are not well understood. We measured the basal area of rapidly growing Pinus taeda trees exposed to free‐air CO 2 enrichment for 8 years and used these measurements to estimate monthly and annual growth. We used these measurements in a statistical model to estimate the start and end of growth in each year. Elevated CO 2 increased the basal area increment ( BAI ) of trees by 13–27%. In most years, exposure to elevated CO 2 increased the growth rate but not the duration of the active growth period. With the exception of 1 year following an extreme drought and a severe ice storm, BAI was positively correlated with the amount of rainfall during the active growth period. The interannual variation in the relative enhancement of BAI caused by elevated CO 2 was strongly related to temperature and rainfall, and was greatest in years with high vapor pressure deficit. There was no evidence of a systematic reduction in the stimulation of growth during the first 8 years of this experiment, suggesting that the hypothesized limitation of the CO 2 response caused by nitrogen availability has yet to occur.

Transition from Planktonic to Benthic Algal Dominance Along a Salinity Gradient - Richard D. Segal; Anya M. Waite; David P. Hamilton (Hydrobiologia, 2006)

Disaggregation of Microcystis aeruginosa colonies under turbulent mixing: laboratory experiments in a grid-stirred tank - Katherine R. O’Brien; David L. Meyer; Anya M. Waite; Gregory N. Ivey; David P. Hamilton (Hydrobiologia, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Qualification of analytical instruments for use in the pharmaceutical industry: A scientific approach - Surendra K. Bansal; Thomas Layloff; Ernest D. Bush; Marta Hamilton; Edward A. Hankinson; John S. Landy; Stephen Lowes; Moheb M. Nasr; Paul A. St. Jean; Vinod P. Shah (AAPS PharmSciTech, 2004)

Simple mixing criteria for the growth of negatively buoyant phytoplankton - Katherine R. O'Brien; Gregory N. Ivey; David P. Hamilton; Anya M. Waite; Petra M. Visser (Limnology and Oceanography, 2003)
Phytoplankton population dynamics are controlled by the relative rather than absolute timescales of mixing, growth, and loss processes such as sedimentation, grazing, and so on. Here, the vertical distribution and biomass of phytoplankton populations are quantified by two timescale ratios: the Peclet number Pe—the ratio of mixing and sedimentation timescales—and the growth number G—the ratio of sedimentation and net growth timescales. Three mixing regimes are defined for phytoplankton and other particles. For Pe ≥ 100, the population is translated linearly down the water column over time and will leave the surface mixing layer completely after sedimentation timeτt s . For 0.1 c =— s /(G —1). This analysis is valid for negatively buoyant phytoplankton, except when mixing time is much longer than growth time and Pe≤ 0.1, which can occur for very slow sinking species. These regimes can be used for assessing the effect of changes in the mixing, growth, or sedimentation conditions on population dynamics. Published data from a lake and diurnally stratified river weir pool are used here to verify a minimum thermocline depth hypothesis proposed by others. Mixing and growth regimes are used to calculate minimum mixing depth h min and to determine phytoplankton sinking rates from published sediment trap data.

World‐wide genetic differentiation of Eubalaena : questioning the number of right whale species - H. C. Rosenbaum; R. L. Brownell; M. W. Brown; C. Schaeff; V. Portway; B. N. White; S. Malik; L. A. Pastene; N. J. Patenaude; C. S. Baker; M. Goto; P. B. Best; et al. (Molecular Ecology, 2000)
Few studies have examined systematic relationships of right whales ( Eubalaena spp.) since the original species descriptions, even though they are one of the most endangered large whales. Little morphological evidence exists to support the current species designations for Eubalaena glacialis in the northern hemisphere and E. australis in the southern hemisphere. Differences in migratory behaviour or antitropical distribution between right whales in each hemisphere are considered a barrier to gene flow and maintain the current species distinctions and geographical populations. However, these distinctions between populations have remained controversial and no study has included an analysis of all right whales from the three major ocean basins. To address issues of genetic differentiation and relationships among right whales, we have compiled a database of mitochondrial DNA control region sequences from right whales representing populations in all three ocean basins that consist of: western North Atlantic E. glacialis , multiple geographically distributed populations of E. australis and the first molecular analysis of historical and recent samples of E. glacialis from the western and eastern North Pacific Ocean. Diagnostic characters, as well as phylogenetic and phylogeographic analyses, support the possibility that three distinct maternal lineages exist in right whales, with North Pacific E. glacialis being more closely related to E. australis than to North Atlantic E. glacialis . Our genetic results provide unequivocal character support for the two usually recognized species and a third distinct genetic lineage in the North Pacific under the Phylogenetic Species Concept, as well as levels of genetic diversity among right whales world‐wide.

Minor Constituent Concentrations Measured from a High Altitude Aircraft Using High Resolution Far-Infrared Fourier Transform Spectroscopy - B. Carli; P. Ade; M. Carlotti; U. Cortesi; A. Gignoli; P. Hamilton; M. Lanfranchi; C. Lee; A. R. MacKenzie; A. Phillips (Journal of Atmospheric Chemistry, 2000)

RELATIVE ABUNDANCE OF LARGE WHALES AROUND SOUTH GEORGIA (1979–1998) 1 - M. J. Moore; S. D. Berrow; B. A. Jensen; P. Carr; R. Sears; V. J. Rowntree; R. Payne; P. K. Hamilton (Marine Mammal Science, 1999)
A bstract To assess large‐whale stocks following the cessation of land‐based South Georgia whaling in 1965, we report three independent sighting databases: a cruise in 1997, observations from Bird Island (NW of South Georgia) between 1979 and 1998, and mariner sightings between 1992 and 1997. All species were rare, with sightings of southern right whales being the most common event. Two right whales photographed off South Georgia matched animals known from Peninsula Valdés, Argentina, a population known to be growing at 7% per annum . In contrast, blue and fin whales appeared to be less abundant. A single blue whale mother‐calf pair was observed off the Shag Rocks in February 1997. Extirpation of animals from this particular feeding ground is the most likely reason for ongoing low numbers of all species. Other factors may include competition for krill by traditional predators such as penguins and seals and more recently by humans, an unusually high rate of natural mortality, habitat change such as alteration in sea ice coverage, and/or the impact of ongoing whaling. The history of this critical area of large‐whale habitat and this report demonstrate the need for improved, consistent longterm monitoring of population trends for these depleted stocks.

GENETIC BASIS AND EVOLUTIONARY SIGNIFICANCE OF VENTRAL SKIN COLOR MARKINGS IN NORTH ATLANTIC RIGHT WHALES ( EUBALAENA GLACIALIS ) - C. M. Schaeff; P. K. Hamilton (Marine Mammal Science, 1999)
A bstract Approximately one third of the North Atlantic right whale population has white ventral skin patches. Most white‐marked animals have both a belly and a chin patch, and the distribution of white pigment suggests that the patches represent a single ventral marking that varies in size and location. Population frequencies and cow‐calf inheritance patterns indicate that the white mark is an autosomal recessive trait. There is no evidence to suggest that ventral coloration patterns are currently under selection. White‐marked and black cows appear to experience similar levels of reproductive success based on calving intervals and length of sighting histories. Also, white‐marked animals were equally common among cows and nulliparous adult females and among live vs . dead animals. Male reproductive success could not be tested because calf paternity is not known; white‐marked and black males exhibit similar survival rates. White‐marked cows were more common among females that took some or all of their calves to the Bay of Fundy summer nursery area compared to females that did not visit Fundy. This suggests that female habitat‐use patterns may influence nuclear gene flow. Increased sample sizes and additional markers are needed to further investigate gene flow.

Microsatellite loci reveal highly significant genetic differentiation among Atlantic salmon ( Salmo salar L.) stocks from the east coast of Canada - S. K. J. McConnell; D. E. Ruzzante; P. T. O'Reilly; L. Hamilton; J. M. Wright (Molecular Ecology, 1997)
Allele frequency data from eight microsatellite loci provide evidence of highly significant genetic differentiation among stocks of Atlantic salmon Salmo salar L. from the Bay of Fundy, eastern and north‐western Nova Scotia and Newfoundland. Estimates of genetic structure ( R ST and θ) were significant both among all samples taken from the different geographical locations and among samples from geographical regions for which more than one stock was sampled. Samples from the Bay of Fundy taken from stocks which are phenotypically and behaviourally diverse showed particularly high levels of genetic structure. Rogers', allele sharing and (δμ) 2 distances also revealed significant differences among stock samples and were significantly correlated [Rogers' and (δμ) 2 ] with sea distance between rivers. Results suggest that stocks of Atlantic salmon in eastern Canada are highly diverse genetically and that this should be an important consideration in any management programme for stocks in the area.

Lactate conversion to acetate, CO2 and H2 in cell suspensions of Desulfovibrio vulgaris (Marburg): indications for the involvement of an energy driven reaction - Ishverlal P. Pankhania; Alfred M. Spormann; W. Allan Hamilton; Rudolf K. Thauer (Archives of Microbiology, 1988)